Divergent DNA methylation patterns and gene expression in MYC and CDKN2B in canine transmissible venereal tumors - Keopaseuth, Soukkangna; Pringproa, Kidsadagon; Patchanee, Prapas; Setthawongsin, Chanokchon; Techangamsuwan, Somporn; Chuammitri, Phongsakorn (Veterinary World, 2024)
Background and Aim: Canine transmissible venereal tumor (CTVT), a unique transmissible cancer in dogs, affects the external genitalia and potentially spreads to other parts of the body. While somatic mutations in oncogenic and tumor-suppressing genes are linked to CTVT development, the impact of DNA methylation, which affects gene expression, remains unclear. This study explored whether DNA methylation in the promoter regions of the MYC oncogene and CDKN2B tumor suppressor genes in CTVTs is associated with their expression, both at the gene and protein levels. Materials and Methods: To investigate promoter DNA methylation of MYC and CDKN2B in CTVTs, we analyzed frozen tissue samples from genital CTVT (GTVTs) and extragenital CTVT (ETVTs). Genomic DNA was extracted, bisulfite-treated, and analyzed using bisulfite polymerase chain reaction (PCR) and sequencing. The messenger RNA and protein of MYC and CDKN2B were also extracted and assessed by real-time PCR and Western blotting. Matching formalin-fixed, paraffin-embedded blocks were used for immunohistochemical staining to visualize protein distribution in GTVT and ETVT tissues. Results: Although both GTVT and ETVT samples showed MYC promoter methylation, the extent of methylation differed significantly. GTVTs displayed a much higher degree of methylation, potentially explaining the more pronounced downregulation of MYC gene expression and reduction in c-MYC protein levels observed in GTVTs compared with ETVTs. Our data revealed a prevalent hypermethylation pattern in the CDKN2B promoter across both sample types. However, DNA methylation, which was expected to have a suppressive effect, did not correlate with gene/protein expression. GTVTs displayed high protein levels despite significantly reduced CDKN2B expression. Conversely, ETVTs maintained regular CDKN2B expression but exhibited reduced protein production, suggesting a complex interplay between methylation and expression in these tumors. Conclusion: MYC demonstrated a clear association between its promoter methylation status, gene expression, and protein levels; however, CDKN2B lacked this correlation, implying the involvement of methylation-independent regulatory mechanisms and highlighting the need for further investigation. Keywords: canine transmissible venereal tumor, CDKN2B, DNA methylation, MYC, oncogene, tumor suppressor gene.